KEEFEKTIFAN PENERAPAN KONSELING REALITA UNTUK MENINGKATKAN TANGGUNG JAWAB SISWA DALAM BELAJAR DI SMK SIDING PURI LENTENG - Adibah, Devivatul; Priyambodo, Aji Bagus (Flourishing Journal, 2022)
Abstract: The purpose of this study was to test the (want, direction, evaluation, planning) WDEP technique to increase student learning responsibility. Therefore, the researcher intends to find out the extent of the effectiveness of reality counseling using the WDEP technique to increase student learning responsibility. The method in this study is a quantitative approach with a pre-experimental one group pretest posttest design. The experimental design used in this study was pretest → treatment nt → posttest, which involved one class as an experiment. The results of this study indicate differences in students' learning responsibilities before and before receiving treatment. If before getting treatment the level of student learning responsibility was at 58.58% and was in the low category, getting treatment the level of student responsibility increased at 80.04% and entered the medium category, from the data it can be seen that the difference in presentation before and before given treatment that is 21.46%. The analysis technique used was the normality test with significance p= 0.200>0.005, and the paired sample t-test obtained a significance of 0.000 where p= 0.000< 0.05. So it can be concluded that there is a significant difference between the results of the pretest and posttest, which means that the application of reality counseling using the WDEP technique is effective to increase learning responsibility. Keywords: reality counselin;, WDEP technique; learning responsibility. Abstrak Tujuan penelitian ini adalah untuk menguji teknik (want, direction, evaluation, planning) WDEP untuk meningkatkan tanggung jawab belajar siswa. Oleh karena itu peneliti berniat untuk mengetahui sejauh mana efektivitas konseling realitas dengan menggunakan teknik WDEP untuk meningkatkan tanggung jawab belajar siswa. Metode dalam penelitian ini adalah pendekatan kuantitatif dengan Pre-experimental one group pretest posttest design. Desain eksperimen yang digunakan dalam penelitian ini pretest→treatment→posttest, yang melibatkan satu kelas sebagai eksperimen. Hasil penelitian ini menunjukkan terdapat perbedaan tanggung jawab belajar pada siswa sebelum dan sesudah mendapatkan treatment. Jika sebelum mendapatkan treatment tingkat tanggung jawab belajar siswa berada pada 58,58% dan masuk dalam kategori rendah, setelah mendapatkan treatment tingkat tanggung jawab siswa meningkat pada 80,04% dan masuk pada kategori sedang, dari data tersebut dapat dilihat bahwa perbedaan presentase sebelum dan sesudah diberikannya treatment yaitu 21,46%. Adapun teknik analisis yang digunakan uji normalitas dengan signifikansi p= 0,200>0,005, dan uji paired sample t-test diperoleh signifikansi 0,000 dimana p=0,000< 0,05. Maka dapat disimpulkan ada perbedaan yang signifikan antara hasil pretest dan posttest, yang berati penerapan konseling realita dengan menggunakan teknik WDEP efektif untuk meningkatkan tanggung jawab belajar. Kata kunci: konseling realitas; teknik WDEP; tanggung jawab belajar